Hukum Perkawinan Menurut Undang Undang No 16 Tahun 2019 Perubahan Atas Undang-Undang Nomor 1 Tahun 1974 Pasal 7 Ayat 1 Tentang Batas Usia Perkawinan - Rahmad Karyadi (CV. PUSDIKRA MITRA JAYA, 2022)
Marriage is an inner bond between a man and a woman as husband and wife which aims to form a happy and eternal family based on the One Godhead. Islam views marriage as a means of worshiping Allah, following the sunnah of the Messenger of Allah, to develop offspring in a legal bond both in the eyes of law and Islam, in order to achieve happiness in the world and the hereafter in the pleasure of Allah SWT. This study aims to determine the implementation of Law No. 16 of 2019 article 7 paragraph (1) amendments to Law No. 1 of 1974 concerning the age limit for marriage, changes to the age limit for marriage where the age of men and women is the same, namely 19 (nine). twelve) years. Changes in the age limit for marriage were made to improve the legal norms of marriage by increasing the minimum age for marriage for women. The type of research used is qualitative and quantitative research, aiming to obtain a complete picture of the views of the people being studied. The research method carried out by the author is a descriptive qualitative method. From the results of the study, it can be concluded that with the enactment of Law Number 16 of 2019 Article 7 paragraph (1) concerning the age limit for marriage, it has an impact on the increasing demand for marriage dispensation in PA Stabat Langkat, this is not the main factor to solve the problem of underage marriage. There are other factors that cause marriage dispensation, namely the low legal awareness of the community, educational and economic problems.